Urotensin-II in the lung: A matter for vascular remodelling and pulmonary hypertension? - Djordjevic, Talija; Görlach, Agnes (Thrombosis and Haemostasis, 2007)
Urotensin-II (UII) is an evolutionary conserved peptide which has been initially discovered in the urophysis of the fish goby regulating body fluid composition and vascular tone. Mammalian UII has gained increasing interest since it has been considered as an even more potent vasoconstrictor than endothelin-1, although its efficiency is greatly variable throughout species and vascular beds. More recently, it has been shown that UII, which mediates its action via binding to the G-protein coupled urotensin-II receptor, is not only involved in the regulation of the vascular tone but can also stimulate a variety of signaling cascades in different cells and organs in the body including generation of reactive oxygen species and nitric oxide, activation of MAP kinases, and modulation of gene expression. Indeed, UII can stimulate proliferative processes, affect the extracellular matrix and may even add to a prothrombotic state. Such vascular remodelling processes are, in conjunction with enhanced vasoconstriction, involved in the pathogenesis of pulmonary hypertension, suggesting that UII may play a novel role in the pathogenesis of this disorder.
Keywords: Urotensin-II; oxidative stress; signal transduction; vascular remodeling; pulmonary hypertension